The Economic and Social Implications of Negative Externalities in Nickel Mining - Kusuma, Jony Puspa; Ananda, Candra Fajri; Khusaini, Moh.; Manzilati, Asfi (Archives of Business Research, 2023)
This research provides an in-depth understanding of the externalities caused by nickel mining and the importance of communities taking collective action against mining activities in Kolaka Regency. This research focused on sea cucumber fishing households in Tambea Village, Pomalaa Sub-district. In some cases, companies with an IUP can carry out practices that can cause harm to the community and the surrounding environment. Environmental contamination, restricted access to land, and economic limitations are the main issues affected communities face. In the face of adverse economic and social implications due to the negative externalities of nickel mining, sea cucumber fishermen have taken collective action and realized the importance of advocating for their rights and protecting the environment and natural resources that support their livelihoods. To address these negative externalities, we need a comprehensive policy design. Qualitative approach This research uses data collection techniques. The data collected in the case study came from participant narratives, direct observation, and analysis of relevant documents that can provide an in-depth understanding of the unique context, with qualitative analysis revealing a wealth of information and detailed details. The location of the case study research is in a village called Tambea Village, Pomalaa District, Kolaka Regency. The results illustrate the economic and social negative externalities caused by this mining activity to sea cucumber fishermen. The results of this study are expected to be the basis for designing comprehensive policies to reduce the negative impacts of nickel mining and protect fishing communities and the surrounding environment.